Pension reform: Australia and China compared. Issue 4 (2nd October 2017) - Bateman, Hazel; Liu, Kevin
Abstract: Over the past few decades, China's pension system has evolved from separate schemes almost exclusively for urban and public sector workers to one with broad national coverage. In a similar time-frame, successive Australian governments have introduced reforms to Australia's retirement income arrangements in an attempt to increase retirement savings and address age-related pressures on the financing of the publicly provided age pension. This paper compares, contrasts and assesses the pension systems in China and Australia. Although China and Australia are at different stages of economic development and demographic transition and operate quite different pension systems, there are lessons to be learned from each other.